Comparison of surgical and non-surgical methods of treating palatally impacted canines. I - Periodontal and pulpal outcomes - Ling Kwok K.; Ho Christopher T. C.; Kravchuk Olena; Olive Richard J. (Sciendo, 2023)
Inferior periodontal and pulpal outcomes may follow surgical exposure of palatally impacted maxillary canines.